GIS-BASED LANDSLIDE HAZARD ANALYSIS BASED ON WEIGHTED OVERLAY METHOD IN SAMARINDA, EAST KALIMANTAN - Raharjanti, Ni'matul Azizah; Sutan, Syamsidar; Ismunandar, Wisnu; Alam, Fajar; Andhika, Muhammad Wira (Fakultas Teknik Geologi Universitas Padjadjaran, 2023)
Samarinda has experienced a frequent landslide disaster, accounting for 30% from the total disaster occurring in 2019. Based on these data, it is necessary to carry out the analysis on the landslide hazard as the mitigation to minimize the damage that may be caused by the landslides. The research was conducted in GIS based processing, by collecting secondary data supported by field observations and quantitative analysis to produce the landslide hazard map. Slope gradient, geology, soil type, and rainfall are the parameters used to determine the landslide susceptibility zonation in the research area. These parameters are then processed using a weighted overlay method. The zoning results show most of Samarinda is included in the intermediate landslide hazard zone, followed by the high landslide hazard zone, and the low landslide hazard zone which has the narrowest distribution. The high landslide hazard zone has a distribution associated with geological structures identified as fold which are included in the Samarinda anticlinorium and thrust fault in north-south direction. The distribution of the landslide hazard zones indicates that the slope gradient, lithology which consist of sedimentary rock, and fold and fault structures, are the main controlling factors for landslides in Samarinda.